School mental health promotion in Indonesia: a quantitative survey from Surabaya - Margaretha, Margaretha; Azzopardi, Peter S.; Fisher, Jane; Sawyer, Susan M. (Frontiers in Psychology, 2026)
IntroductionMost young people live in low- and middle-income countries (LMICs), yet little is known about the implementation of school mental health promotion strategies in resource-poor settings. This study describes the extent of school mental health promotion and its drivers in junior high schools in Surabaya, Indonesia.MethodsData were obtained from a sample of 161 schools (63 public schools (100% participation), 74 private schools (28.79% participation), and 24 madrasas (42.85% participation)) using an online survey supported by the Department of Education. Descriptive statistics (ANOVA and Chi-square tests) were used to analyse data.ResultsMost programs addressed mental health as part of comprehensive school health strategies derived from national and local policies. Implementation was reported through five key programs: 1) health-promoting school strategies through the school health unit, 2) safe and healthy school environments through child-friendly schools, 3) support through peer counsellors, 4) mental health as an extra-curricular health education module, and 5) mental health risk assessments to inform school interventions. Public schools reported the highest success in implementing these programs. Madrasas scored lower across all programs.DiscussionWhile school mental health promotion is acknowledged through national policies, its implementation in Indonesia appears to be challenging. The development of national standards, investment in school leadership, and support for broader collaboration, especially among ministries of education, religion, and health, could enhance the implementation of school mental health promotion in Indonesia.